Letter to Jane Tolmach; From Al Vercoutere - Al Vercoutere:::::: (1968)
This letter to Jane Tolmach from Al Vercoutere (Administrative Assistant) sent on March 5, 1968 confirms the telephone conversation regarding travel arrangements to Porterville State Hospital on March 28, 1968.